2008
DOI: 10.1371/journal.pone.0001637
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Immunoglobulin-Immunoglobulin Interaction in Autoimmunity

Abstract: Well over six decades since its first description, the Rheumatoid Factor (RF)—autoantibodies recognizing Fc (constant) portion of IgG through their own Fab (antigen binding variable segments)—is believed to have come of age. Autoimmune pancreatitis is a unique form of pancreatitis, biologically characterized by an elevated serum IgG4 concentration. Given the fact that IgG4 myeloma proteins can act as RF, we initially hypothesized that IgG4 in autoimmune pancreatitis might do likewise, hence potentially contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 44 publications
1
78
2
Order By: Relevance
“…Thus the high prevalence of IgG4-type cTnAAbs may also explain why our attempts to develop bridge-type immunoassays that use the same antigen as a capture and a tracer for cTnAAb detection have not succeeded (results not shown). Another feature of IgG4-type antibodies is that they may have a high affinity for various animal IgGs, such as mouse IgG, via their constant regions rather than their antigen-binding sites (26,27 ). If cardiac troponin-specific IgG4s bind to animal IgGs used as immunoassay reagents, then in addition to blocking specific cardiac troponin epitopes, they could potentially interfere with cardiac troponin immunoassays nonspecifically.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the high prevalence of IgG4-type cTnAAbs may also explain why our attempts to develop bridge-type immunoassays that use the same antigen as a capture and a tracer for cTnAAb detection have not succeeded (results not shown). Another feature of IgG4-type antibodies is that they may have a high affinity for various animal IgGs, such as mouse IgG, via their constant regions rather than their antigen-binding sites (26,27 ). If cardiac troponin-specific IgG4s bind to animal IgGs used as immunoassay reagents, then in addition to blocking specific cardiac troponin epitopes, they could potentially interfere with cardiac troponin immunoassays nonspecifically.…”
Section: Discussionmentioning
confidence: 99%
“…Although elevated serum IgG4 levels define the presence of IgG4-RD-associated inflammation in a variety of organs, and thus it is essential for disease diagnosis, the pathophysiological role of this elevated Ig subtype is poorly understood. On one hand, elevated IgG4 levels may be an epiphenomenon associated with IgG4-RD-associated chronic inflammation, because this IgG subtype exhibits limited ability to bind to complement and FcgRs (5,6) and has been shown to have anti-inflammatory activity in experimental myasthenia gravis (7). On the other hand, enhanced IgG4 levels may play a vital immunopathologic role in this disease, because IgG4 Abs against autoantigens have also been shown to participate in the pathogenesis of autoimmunity (8,9).…”
mentioning
confidence: 99%
“…Few reports regarded IgG4-type autoantibodies as pathogenic in type 1 AIP. IgG4 was recently discovered to have two outstanding characteristics, Fab-arm exchange [43] and rheumatoid factor-like activity [44], both of which may play immunedefensive roles by eliminating IgG4-bound immune complex from the circulation. Fab-arm exchange results in bispecific antigen binding, which interferes with the formation of IgG4-associated immune complexes [44].…”
Section: Serological Characteristicsmentioning
confidence: 99%
“…IgG4 was recently discovered to have two outstanding characteristics, Fab-arm exchange [43] and rheumatoid factor-like activity [44], both of which may play immunedefensive roles by eliminating IgG4-bound immune complex from the circulation. Fab-arm exchange results in bispecific antigen binding, which interferes with the formation of IgG4-associated immune complexes [44]. It was also demonstrated that IgG4 can bind to another IgG of any subclass via Fc-Fc interaction, and this IgG4 Fc-Fc interaction may represent an intermediate state of the Fab-arm exchange reaction [44][45][46][47], although the role of this function remains unclear.…”
Section: Serological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation